Hyperthermic fatigue precedes a rapid reduction in serum sodium in an Ironman triathlete: A case report - Laursen, P. B.; Watson, G.; Abbiss, C. R.; Wall, B. A.; Nosaka, K. (International Journal of Sports Physiology and Performance, 2009)
Purpose: To monitor the hydration, core temperature, and speed (pace) of a triathlete performing an Ironman triathlon. Methods: A 35-year-old experienced male triathlete participated in the Western Australian Ironman triathlon on December 1, 2006. The participant was monitored for blood Na+ concentration before the race (PRE), at the transitions (T1 and T2), halfway through the run (R21), and after the race (POST; 2hPOST). Core body temperature (Tc; pill telemetry) was recorded continuously, and running speed (s3 stride sensor) was measured during the run. Results: The participant completed the race in 11 h 38 min, in hot conditions (26.6 ± 5.8°C; 42 ± 19% rel. humidity). His Tc increased from 37.0 to 38.6°C during the 57-min swim, and averaged 38.4°C during the 335-min bike (33.5 km/h). After running at 12.4 km/h for 50 min in the heat (33.1°C), Tc increased to 39.4°C, before slowing to 10.0 km/h for 20 min. Tc decreased to 38.9°C until he experienced severe leg cramps, after which speed diminished to 6 km/h and Tc fell to 38.0°C. The athlete`s blood Na+ was constant from PRE to T2 (139-140 mEq/L, but fell to 131 mEq/L at R21, 133 mEq/L at POST, and 128 mEq/L at 2hPOST. The athlete consumed 9.25 L of fluid from PRE to T2, 6.25 L from T2 to POST, and lost 2% of his body mass, indicating sweat losses greater than 15.5 L. Conclusion: This athlete slowed during the run phase following attainment of a critically high Tc and experienced an unusually rapid reduction in blood Na+ that preceded cramping, despite presenting with signs of dehydration.